Effect of Ephedra alata Decne. on lipids metabolism of Aspergillus flavus Link - Al-Qarawi, AA; Allah, EF Abd; Abeer, Hashem (Bangladesh Journal of Botany, 2013)
In Aspergillus flavus Link, the total lipid, sterols, neutral lipids, phospholipids and fatty acid content decreased significantly with the application of different concentrations of Ephedra alata Decne. extrtact. Gas chromatographic analysis revealed the presence of 12 fatty acids namely, (caprylic (C8), capric (C10), lauric (C12), myristic (C14), palmitic (C16), palmitoleic (C16:1), stearic (C18), oleic (C18:1), linoleic (C18:2), ? linolenic (C18:3), arachidic (C20) and arachidonic (C20:4) with total un-saturation per cent 69.78 in the cellular lipids of A. flavus. The use of E. alata extracts induced significant alteration in fatty acid profile towards increment saturation. DOI: http://dx.doi.org/10.3329/bjb.v42i1.15823 Bangladesh J. Bot. 42(1): 45-49, 2013 (June)